(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
The study was conducted during the years 2016 - 2017 in order to obtain the best rate of germination of the seeds of the Gleditsia triacanthos and the search for the best conditions for the growth of its seedlings and thus get the plantings with a quality required for afforestation. Three treatments were tested which seeds were soaked in hot water (80 c) at three times (24,48 and 72 hours) ,and then grown in special pots containing three agricultural media (turf,nursery soil and mixed of turf and nursery soil 1:1) The study found that The 48-hour soaking treatment achieved the best percentage of germination and the highest percentage of germination was found in the turf substrate and was significantly superior to the rest of the agricultural substrates used, and gave the best values ​​for the shoot and root systems of the developing Gleditsia seedlings ., and the positive effect of turf substrate improved the values ​​of measured indicators during its mixing with forest nursery soil. Thus, it is possible to modify the values ​​of the nursery soil through the mixing process with the turf. أجريت الدراسة خلال العامين 2016 - 2017 بهدف الحصول على أفضل نسبة لإنبات بذور الغلاديشيا والبحث عن افضل الشروط لنمو بادراته والحصول بالتالي على غراس تمتاز بالجودة المطلوبة لأعمال التشجير. تم نقع البذور بالماء الساخن (80) درجة مئوية في ثلاث معاملات (24 ساعة-48 ساعة-72 ساعة ) وزرعت البذور في أوعية خاصة تحوي ثلاث أوساط زراعية (تورف-تربة المشتل-وخليط من التورف وتربة المشتل بنسبة 1:1 ) بينت الدراسة أن معاملة نقع البذور لمدة 48 ساعة حققت النسبة المئوية الأفضل في الإنبات. وخلصت الدراسة إلى ان أعلى نسبة انبات كانت في وسط التورف وتفوق معنوياً على باقي الأوساط الزراعية المستخدمة, وأعطى أفضل القيم الخاصة بالمجموعين الخضري والجذري لبادرات الغلاديشيا النامية. كما ظهر التأثير الإيجابي للتورف في تحسين قيم مؤشرات النمو المقاسة عند خلطه مع تربة المشتل الحراجي ، وبالتالي إمكانيّة تحسين بعض خصائص وسط تربة المشتل من خلال عملية الخلط مع التورف.